Philodina alata Murray 1910 - LUKASHANETS, Dzmitry A.; VEZHNAVETS, Vasily V.; MAYSAK, Natalia N.; HIHINIAK 1, Yury H.; BORODIN, Oleg I.; MIAMIN, Vladislav Ye.; GAIDASHOV, Alexey A.; NIKITIUK, Leonid A. (Zenodo, 2019)
Philodina alata Murray, 1910 Philodina alata Murray 1910: 46 – Donner 1965: 207, Kutikova 1991: 93, 95, Kutikova 2005: 207 Notes. All individuals in plankton samples are contracted but could be identified by two characteristic lateral appendages. Published as part of LUKASHANETS, Dzmitry A., VEZHNAVETS, Vasily V., MAYSAK, Natalia N., HIHINIAK 1, Yury H., BORODIN, Oleg I., MIAMIN, Vladislav Ye., GAIDASHOV, Alexey A. & NIKITIUK, Leonid A., 2019, Rotifers (Rotifera) from the inland waters and terrestrial habitats of East Antarctic oases (Enderby Land and Prydz Bay), pp. 67-86 in Fragmenta Faunistica 62 (2) on page 75, DOI:10.3161/00159301FF2019.62.2.067, http://zenodo.org/record/6252396